Effect of acupuncture in the acute phase of intracerebral hemorrhage on the prognosis and serum BDNF: a randomized controlled trial - Li, Lingcong; Wang, Xiujing; Guo, Jiaxun; Chen, Yilin; Wang, Zhenyu (Frontiers in Neuroscience, 2023)
BACKGROUND: Intracerebral hemorrhage (ICH) is a common cerebrovascular disease, with a high rate of disability. In the literature on Chinese traditional medicine, there is increasing evidence that acupuncture can help hematoma absorption and improve neurological deficits after cerebral hemorrhage. Brain-derived neurotrophic factor (BDNF), one of the most studied neurotrophic factors, is involved in a variety of neurological functions and plays an important role in brain injury recovery. We investigated the effect of acupuncture intervention in the acute phase of ICH on the prognosis and serum BDNF levels of several patient groups. OBJECTIVE: To investigate the influence of acupuncture on the prognosis and brain-derived neurotrophic factor (BDNF) levels in patients in the acute phase of ICH. METHODS: From November 2021 to May 2022, 109 subjects were consecutively enrolled, including patients with ICH, who were randomized into the acupuncture group (AG) and sham acupuncture group (SAG), and a control group (CG). The CG received the same acupuncture intervention as the AG, and the SAG received sham acupuncture, with 14 interventions in each group. The level of consciousness of patients with ICH was assessed and serum BDNF levels were measured in all three groups before the intervention and at 3 weeks after onset, and the level of consciousness and outcomes were assessed at 12 weeks after onset. RESULTS: After the intervention, the level of consciousness of the AG improved significantly (P<0.05); the BDNF level of only the AG increased significantly (P<0.05); the changes in Glasgow Coma Scale (GCS) score and BDNF level were significantly greater in the AG than in the SAG (P<0.05), especially for locomotion (P<0.05). At 12 weeks post-onset, the AG showed better outcomes and recovery of consciousness than the SAG (P<0.05).